Analysis of Chinese EFL Lecturers’ Attitude Toward Online Professional Development - Lingdi, Kong; Khaliza, Saidin; Mohd Kasri, Saidon; Haihong, Yang (American Scientific Publishers, 2018)
The significance of applying information and communication technology to alleviate a series of training problems in teacher education has been proved and accepted widely.However, Chinese researchers found that less than 50% teachers were strongly willing to involve in their online professional development (OPD) courses.Therefore, research objective of this study was to identify the level of Chinese EFL lecturers’ attitudes toward attending OPD courses on the basis of identification of the relationship among five dimensions referred to attitudes toward OPD, including the usefulness of OPD, ease of use in OPD, affection happened in OPD, anxiety involved in using OPD and behaviors in their future plans on OPD.The respondents consisted of 98 Chinese EFL lecturers from 4 universities in Ningxia.The instrument for data collection was the 28-item questionnaire for the study.The researchers adopted the Cronbach Alpha method to determine the reliability of the instrument.A reliability index of 0.82 was obtained.Two research questions were structured and data collected were analyzed using SPSS 2.0. Overall, this study shows that perceived usefulness and ease of use are high among sampled of Chinese EFL lecturers’ attitude toward their OPD.Besides, anxiety has a significant effect on the professional development of teachers. It is also recommended that OPD courses should be tailored toward EFL lecturers’ professional development needs.This would help them to raise their willingness as well as enthusiasm and have good reason to participate OPD courses.